(untitled) (Albayan Scientific Journal, 2023)
This study was conducted to find out the effect of age on body weight and some external physical characteristics and the correlation coefficient of live body weight with these characteristics on 9 female of libyan Barbary lambs from the age of weaning (three months) until the age of marketing in the Belges region of Jabal Al-Akhdar - Libya. The study was conducted from March to May 2019 and measurements were taken every two weeks and lasted for two months. The results were as follows: Body weight recorded a significant P<0.001 increase during the trial period until the marketing age, and the average daily weight gain was about 106 g. There was also a significant increase P<0.01 in both body length, shoulder height, chest circumference (girth) and ear length (cm) at the marketing age compared to the age at the beginning of the experiment. The results also showed that the correlation coefficient (R2) of live body weight with some external physical characteristics recorded higher with shoulder height (0.80), body length (0.73) and chest circumference (0.63), and linear equations were made to predict live body weight.It can be concluded that